Sobre práticas religiosas e culturais islâmicas no Brasil e em Portugal: notas e observações de viagem - Vera Lucia Maia Marques (2009)
Since September 11th 2001, debates over Islam have been intensified in search for plausible explanations for the terrorist attacks to the World Trade Center. Questions on what Islam is and what it says about violence, terrorism and democracy have been at stake, above all in the medianowadays, one of the most important information sources as well as for building our cognitive worlds. It is also the mass vehicle the one that allows a larger visibility of the Muslims due to the dilemmas and conflicts arisen from those images. Inspired by the scenario as well as by the growing number of Muslims in the world, I decided to travel amongst those religious practices and the Islamic cultural practices in Brazil and in Portugal in order to observe and notice the richly woven texture in the relations between religion and culture, tradition and modernity. Two fields: different origins, religious tendencies, schools of thought, religious movements, here and there, which have resulted not only in diversity, but also in conflicts. And, as a contemporaneous manifestation in which spiritual renewal and social-cultural contexts change into the idea of cultures or religious, formerly inherited and now chosen, the converted ones find themselves inserted also. Thus, with the aim of better understanding the complex Islamic religious and cultural field, through a focus of analysis enlarged as to reach Muslims by birth and Muslims through conversion, I have attempted to understand, in field, the differences that also unite them.